Políticas de currículo para a educação do campo no Rio Grande do Sul: um estudo sobre o conhecimento escolar - Bresolin, Paoline (2016)
This thesis presents a study of the meanings of school knowledge emerging from curriculum policies for Rural Education in Rio Grande do Sul, seeking to link the Curriculum Studies and the area of Rural Education. The constituent scenario of these themes points to marked historical trajectories mainly by the expansion of industrialization in the late nineteenth century and early twentieth century. This expansion led to intense transformation processes over time, regarding content selection and curriculum issues, as well as the involvement of the public and civil spheres bound to the rural context. In order to investigate the curriculum policy for Basic Education of schools in rural areas of Rio Grande do Sul and its relations with the development of school knowledge, we aim to: a) analyze the legal documents that guide these schools, investigating their connections with the curriculum organization; and b) identify and analyze which meanings of school knowledge are present in the documents. Therefore, the study presents the following guiding question: which meanings of school knowledge are privileged in curriculum policies for schools in rural areas of Rio Grande do Sul? This discussion, linked to the theoretical studies developed, reflects a study of qualitative approach. The guiding documents of the curricular policies for Basic Education Schools of rural areas of the Rio Grande do Sul state are used as empirical corpus. In order to support the theoretical arguments, we start from a pluralistic approach in order to consider different ideas and broaden our understanding of the subject. The study revealed the possibility of expanding learning opportunities for students through school knowledge, by providing curricula that create opportunities to transcend the experiential level. After detailed and attentive analysis, we found four meanings of school knowledge used in the documents’ discourse. Two of them were anchored in theories about social justice, especially by Nancy Fraser, indicating that the education processes of rural areas would need to be guided by the triad redistribution, recognition and participation, focusing its social aspect under the Curriculum Studies. The other two senses were supported in the conceptualizations produced around the notion of curriculum differentiation, directing the arguments to discussions that are contributing to the curriculum organization, considering the variety of educational purposes when compared to the cultural diversity.